2001
DOI: 10.1021/jo010386b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Enantiomeric Synthesis of Pyrrolidine and Piperidine Alkaloids from Tobacco

Abstract: An enantiomeric synthesis of six piperidine and pyrrolidine alkaloids, (S)-nornicotine 1, (S)-nicotine 2, (S)-anatabine 3, (S)-N-methylanatabine 4, (S)-anabasine 5, and (S)-N-methylanabasine 6, known as natural products in tobacco, was established from a common chiral homoallylic (S)-3-(1-azido-but-3-enyl)-pyridine 15. An intramolecular hydroboration-cycloalkylation of the homoallylic azide intermediate 15 served as the key step in the pyrrolidine ring formation. A ring closing metathesis reaction (RCM) of a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(70 citation statements)
references
References 49 publications
2
66
0
2
Order By: Relevance
“…HRMS (FABþ) m∕z calculated for C 10 H 14 N [M þ H]: 148.1126, found 148.1134. To establish enantiomeric excess, the product was converted to ethyl 2-phenylpyrrolidine-1-carboxylate via a previously described procedure (40), and this material was evaluated by analytical chiral HPLC analysis using a Chiralcel OD-H column (4.6 mm × 25 cm) from Daicel Chemical Industries, Ltd., with 2% isopropyl alcohol in hexanes, giving an enantiomeric excess of 96%. 1 Enantioenriched 2-phenylpyrrolidine from above, (0.13 g, 0.86 mmol) was added to a two-neck, 25-mL round-bottom flask equipped with a reflux condenser.…”
Section: Methodsmentioning
confidence: 99%
“…HRMS (FABþ) m∕z calculated for C 10 H 14 N [M þ H]: 148.1126, found 148.1134. To establish enantiomeric excess, the product was converted to ethyl 2-phenylpyrrolidine-1-carboxylate via a previously described procedure (40), and this material was evaluated by analytical chiral HPLC analysis using a Chiralcel OD-H column (4.6 mm × 25 cm) from Daicel Chemical Industries, Ltd., with 2% isopropyl alcohol in hexanes, giving an enantiomeric excess of 96%. 1 Enantioenriched 2-phenylpyrrolidine from above, (0.13 g, 0.86 mmol) was added to a two-neck, 25-mL round-bottom flask equipped with a reflux condenser.…”
Section: Methodsmentioning
confidence: 99%
“…8) Myosmine, which was isolated from Nicotina tabacum, is structurally related to anabaseine; myosmine has a pyrrolidine heterocyclic ring, while anabaseine has a piperidine ring. 9) It has been found that 3-pyridylmethylamine moiety, containing a highly basic nitrogen atom protonated at physiological pH, is the essential moiety for nicotinoid toxicity. 10) We became interested in the affinity of 3-benzylidene-and 3-cinnamylidenemyosmine analogues for insect nAChRs, even if myosmine itself, with low basic nitrogen, has little binding affinity for housefly and honeybee nAChRs.…”
Section: Introductionmentioning
confidence: 99%
“…Felpin et al achieved an efficient enantiomeric synthesis of tobacco alkaloids. 27 Syntheses of non-radiolabeled (+) anatabine were also reported by Quan et al 28 and by Hoffmann et al 29 We have followed a similar approach for the synthesis of (+) [5-…”
Section: Resultsmentioning
confidence: 94%